Incidence and Prognostic Implication of Bone Marrow Involvement in Hodgkinâ€™s Lymphoma - Bansal, Rimpi; Kaur, Puneet; Sarin, Jatin; Kaur, Anureet; Sarin, Akshita (Annals of Pathology and Laboratory Medicine, 2021)
Introduction- : Conducting Bone marrow examination in a Hodgkin's Lymphoma (HL) patient at the time of diagnosis is done routinely to determine the stage of the disease. The aim of this study was to analyze the incidence and prognosis of bone marrow involvement in patients with Hodgkins lymphoma, retrospectively. Materials and Patients: Ten patients of Hodgkins lymphoma were incorporated in the current study. Bone marrow aspiration and biopsy was done in all ten cases as part of staging procedure. Results: Three patients showed involvement of bone marrow by Hodgkinâ€™s lymphoma and both the patients had clinically poor outcome. Discussion and Conclusion: Bone marrow examination is important in stage II and III of Hodgkinâ€s lymphoma because positive result will upstage the disease. Also, bone marrow involvement indicates an aggressive disease and poor prognosis for the patient.